2011
DOI: 10.1586/eem.11.24
|View full text |Cite
|
Sign up to set email alerts
|

The hedgehog/Gli signaling paradigm in prostate cancer

Abstract: Hedgehog is a ligand-activated signaling pathway that regulates Gli-mediated transcription. Although most noted for its role as an embryonic morphogen, hyperactive hedgehog also causes human skin and brain malignancies. The hedgehog-related gene anomalies found in these tumors are rarely found in prostate cancer. Yet surveys of human prostate tumors show concordance of high expression of hedgehog ligands and Gli2 that correlate with the potential for metastasis and therapy-resistant behavior. Likewise, prostat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 129 publications
(22 reference statements)
2
22
0
Order By: Relevance
“…Previously, aberrant HH signaling in prostate tumors was reported to be ligand-dependent, although it is controversial whether this is in a paracrine or autocrine manner (3). In fact, the HH pathway is part of a complex signaling network that remains incompletely understood (9).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, aberrant HH signaling in prostate tumors was reported to be ligand-dependent, although it is controversial whether this is in a paracrine or autocrine manner (3). In fact, the HH pathway is part of a complex signaling network that remains incompletely understood (9).…”
Section: Discussionmentioning
confidence: 99%
“…In spite of early detection techniques and multidisciplinary therapeutic approaches, the overall 5-year survival rate remains <30% in China (2). Anti-androgen treatment remains the first-line therapy for patients with prostate cancer, among whom the majority will eventually develop highly metastatic androgen-independent prostate cancer (3). Prostate cancer is a complex and heterogeneous disease characterized by various molecular signatures in patients, which provides opportunities to explore targeted therapies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Foreword the IL-6/AR interaction, which is both stimulatory and inhibitory to prostate cancer cells [5]; and the interaction between Gli proteins and AR, which implicates hedgehog and androgen signaling pathways [6]. The role of androgens in epithelial-mesenchymal transition and mesenchymal-epithelial transition provide further need to block androgen action and metastatic spread [7].…”
Section: For Reprint Orders Please Contact Reprints@expert-reviewscommentioning
confidence: 99%
“…Furthermore, EGFR expression increases during progression to a hormone-resistant stage (15)(16)(17). Previous studies have demonstrated that epidermal growth factor (EGF) signaling and Hedgehog (HH) signaling are both involved in prostate cancer tumorigenesis and progression (18)(19)(20)(21)(22)(23); however, whether there is any 'crosstalk' between these two important pathways requires clarification. In the present study, we mainly explored the role of GLI-1, which is the transcription factor of HH signaling, in EGF-regulated enhancement of the invasiveness of ARCaP E prostate cancer cells in vitro.…”
Section: Introductionmentioning
confidence: 99%